محدثو القراء السبعة (The hadith scholars of the seven qira’at) - Mohd A'tarahim, Mohd Razali; Abdillah Hisham, Ab. Wahab; Ahmad Zahid, Salleh (2020)
The sciences of Islamic jurisprudence and legitimacy were mixed then expanded and later branched into different sciences. However, the specializations and methods, which people used to follow, today made many students of Qira’at (readings) ignorant of the various Sharia sciences, which created a gap between students of the science of Qira’at (readings) and the various sciences of Sharia. Herein lies the problem. The researcher considered it important to write about the hadith scholars of the Seven Qira’at (readings), explain their positions, and rank in the science of hadith. The purpose of this study is to explain the path taken by the righteous ancestors in the study of Islamic sciences, using the analytical and descriptive method. From the results, it appeared to us: that all the seven reciters have a (chain of) narration in the hadith, whether it is less or many. In addition, that Hamzah bin Habib is the best scholar of the seven Qira’at (readings) and the most authentic of them by narration, knowledge, jurisprudence and piety. Moreover, his narrated hadiths are in the books of the Sihah such as Sahih al-Bukhari. In addition, not everyone who is strong in Qira’at (readings) and proficient in it is considered an authority to the scholars of hadith. Moreover, that the Qira’at reader's weakness in the hadith does not affect his quality of Qira’at (reading), because the Qira’at (reading) is frequent and the agreement and consensus of the Islamic community has fallen on it since ancient times. Allah knows the best.